A PRAGMATIC STUDY OF SPEECH ACTS USED IN SHORT MESSAGE SERVICE (SMS) BY ENGLISH DEPARTMENT STUDENTS OF RIAU KEPULAUAN UNIVERSITY - Megah, Suswanto Ismadi (Universitas Riau Kepulauan, 2012)
The developing science and knowledge are followed by the advanced technology. Those significantly have contributed in communication by inventing cellular or mobile phone by performing written message. These become a phenomenon in society recently by communicating via SMS. These are a natural phenomenon of cellular user by sending SMS (Short Message Service). SMS normally is used by the teenager in sending message. In addition, SMS language can be categorized as a unique language, because the users do not use the standard language to write messages (SMS). The data obtained from the English Students who have studied pragmatics.The most dominant use of type of directives while the functions are asking and requesting used more often used thn the other types. While the usage of the numbers and alphabets to change the letters based on the phones due to minimizing or shortening the words used.Â